2008
DOI: 10.1051/mmnp:2008032
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni Convection in a Photo-Chemically Reacting Liquid

Abstract: Abstract. Marangoni convection caused by a photochemical reaction of the type A hν B in a deep liquid layer is studied. Linear stability analysis is performed and the conditions for Marangoni convection to occur are obtained. It is shown that increasing the rate of the direct reaction, for example, by increasing the light intensity, destabilizes the steady state and causes convective motion of the fluid, whereas increasing the rate of the inverse reaction stabilizes the steady state. A weakly nonlinear analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As our group demonstrated in recent experiments,21 by patterning surface energy gradients into a solid thin polymer film, the Marangoni effect can be harnessed to direct flow in the melt state. It is important to note that previous theoretical studies82–84 have explored similar ideas, although some of the details are different.…”
Section: Directing Convection In Polymer Films By Photochemical Pattementioning
confidence: 99%
“…As our group demonstrated in recent experiments,21 by patterning surface energy gradients into a solid thin polymer film, the Marangoni effect can be harnessed to direct flow in the melt state. It is important to note that previous theoretical studies82–84 have explored similar ideas, although some of the details are different.…”
Section: Directing Convection In Polymer Films By Photochemical Pattementioning
confidence: 99%
“…Another interesting feature of this process is that upon significant additional heating of the film above its T g , on the order of hours, the features dissipate resulting in a featureless, flat film. Marangoni flow in liquids driven by reversible photochemical reactions in Newtonian liquids has previously been examined from a theoretical standpoint. , While the photochemical reaction of PS is in principle irreversible, these studies describe an interesting theoretical framework for consideration in future experiments.…”
mentioning
confidence: 99%
“…Chowdhury et al reported on experiments regarding UV-induced photopolymerization reactions of aniline films floating on water. Golovin and Volpert , studied the Marangoni instability of a thin liquid layer subject to uniform illumination that triggers a reversible photochemical reaction. They performed a linear stability analysis as well as numerical simulations of the evolution equations for the height and reactant concentration profiles.…”
Section: Introductionmentioning
confidence: 99%